2016
DOI: 10.1523/jneurosci.1748-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalized Microfluidic Platforms: The Unrivaled Breakthrough ofIn VitroTools for Neurobiological Research

Abstract: Microfluidic technology has become a valuable tool to the scientific community, allowing researchers to study fine cellular mechanisms with higher variable control compared with conventional systems. It has evolved tremendously, and its applicability and flexibility made its usage grow exponentially and transversely to several research fields. This has been particularly noticeable in neuroscience research, where microfluidic platforms made it possible to address specific questions extending from axonal guidanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
108
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(110 citation statements)
references
References 103 publications
0
108
0
Order By: Relevance
“…Since the implementation of the compartmentalized neuronal cell culture [1] years ago [2,3], microfluidic technology, micropatterning, and microfabrication allowing spatial and fluidic segregation of neuronal soma from axons [4] have greatly improved. This technology has permitted real-time monitoring of physiological events, thus becoming a key reference technique for many researchers and laboratories (see also [5,6] for review). Additionally, some studies have also reported different ways to lesion axons on lab-on-chip devices (i.e., [7]).…”
Section: Introductionmentioning
confidence: 99%
“…Since the implementation of the compartmentalized neuronal cell culture [1] years ago [2,3], microfluidic technology, micropatterning, and microfabrication allowing spatial and fluidic segregation of neuronal soma from axons [4] have greatly improved. This technology has permitted real-time monitoring of physiological events, thus becoming a key reference technique for many researchers and laboratories (see also [5,6] for review). Additionally, some studies have also reported different ways to lesion axons on lab-on-chip devices (i.e., [7]).…”
Section: Introductionmentioning
confidence: 99%
“…Developments in the field of microfluidics may also play an important role in improving the physiological relevance of in vitro models for neurological diseases and the use of iPSCderived neurons in drug screening (reviewed recently in Neto et al, 2016;Nys and Fillet, 2018;Regnault et al, 2018). The field of microfluidics is relevant to drug screening for several reasons.…”
Section: Technical Limitations and Potential Future Advancesmentioning
confidence: 99%
“…The use of microfluidic systems and tools for neurobiology applications has been recently reviewed. [2630] In this section, we limit the discussion to representative examples of microfluidic systems in the content of neuropathology.…”
Section: Recapitulating the Human Brain Pathophysiologymentioning
confidence: 99%
“…[30,49,50] For example, a high-throughput microarray utilizing the compartmentalized microfluidic platform was recently employed for quantitative screening of synaptogenesis in large-scale (Figure 3B). [50] By using this high-throughput platform, authors screened a chemical library that leads to discovery of class I histone deacetylase inhibitors as potential regulators of neuroligin-1-induced synaptogenesis pathway.…”
Section: Recapitulating the Human Brain Pathophysiologymentioning
confidence: 99%